Exploring the Impact of Consumer Vanity on Money Attitude and Compulsive Buying of Branded Products in Indonesia - Elgeka , Honey Wahyuni Sugiharto; Prasistyasaria, Ni Nyoman Mainda (Journal of Ecohumanism, 2024)
Branded products have become a prominent focus for young consumers in Indonesia, often leading to significant expenditures and the development of compulsive buying behaviors. This study explores the mediating role of consumer vanity in the relationship between money attitudes and compulsive buying among undergraduate students in Surabaya, Indonesia. Data were collected from 276 participants using a purposive sampling method. The analysis, conducted with Hayes’ Process Model 4, examined the influence of three money attitude dimensions—power prestige, distrust, and anxiety—on compulsive buying. The findings reveal that consumer vanity significantly mediates the relationships between power prestige (β =.16, CI =.08,.24), distrust (β =.23, CI =.10,.37), anxiety (β =.35, CI =.21,.52), and compulsive buying. These results suggest that young consumers use branded product purchases to project success and align themselves with an affluent lifestyle. Compulsive buying emerges as a behavior through which individuals display power and status, reinforcing the role of consumer vanity in driving such purchases.